Reduplication of Consonant Graphemes in the Ormlum in The Light of Late Old English Scribal Evidence - Mokrowiecki, Tomasz (Studia Anglica Posnaniensia, 2013)
As opposed to previous studies, which usually attempt to refute the traditional interpretation put on the use of double consonants in The Ormulum, and attempt to advance an alternative explanation for the abnormally frequent use of <CC> digraphs, the current study primarily focuses on the standard view, which assumes that the scribe of MS Junius 1 applied double consonant graphemes to indicate vowel shortness. However, in this study the evidence comes not from The Ormulum but from two Late Old English MSS, as the use of double consonants to indicate vowel shortness is also occasionally attested in some earlier texts (Anderson - Britton 1997: 34, 51, 1999: 305, 317-323; Smith 2007: 107; and Laing 2008: 7-8). The major aim of this study is to show that the use of reduplicated consonant graphemes as indicators of vowel shortness is not confined exclusively to The Ormulum because this practice derives directly from Old English scribal tradition, where <CC> sequences were used not only to represent geminate (or long) consonants, but sporadically also for marking short vowels.